2010
DOI: 10.1063/1.3460293
|View full text |Cite
|
Sign up to set email alerts
|

Removal of floating dust in glow discharge using plasma jet

Abstract: Dust can be an inconvenient source of impurities in plasma processing reactors and in many cases it can cause damage to the plasma-treated surfaces. A technique for dust expulsion out of the trapping region in plasma is presented here, based on the wind force exerted on dust particles by a pulsed plasma jet. Its applicability is demonstrated by removing floating dust in the sheath of parallel-plate capacitive radio-frequency plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Experiments have confirmed that the ion drag force can propel the dust particles and accelerates them to speeds up to a few km/s. 10,24,26 The ion drag force is proportional with the plasma density and its flow speed. Our proposed dust removal technique is based on the drag force exerted by the plasma flow at a reduced pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have confirmed that the ion drag force can propel the dust particles and accelerates them to speeds up to a few km/s. 10,24,26 The ion drag force is proportional with the plasma density and its flow speed. Our proposed dust removal technique is based on the drag force exerted by the plasma flow at a reduced pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Clean processing technologies are discussed in a 2002 review paper by Läifa Boufendi and André Bouchoule [195]. One interesting approach makes use of the ion drag force in a pulsed plasma jet for dust expulsion [196].…”
Section: Dusty Plasma Applications: a Double-edged Swordmentioning
confidence: 99%
“…In light of the new ambitions for human space exploration the interest for this type of discharge has been renewed recently since the magnetoplasmadynamic accelerator is one the most powerful form of electric propulsion [27]. The plasma wind force has been exploited in fusion applications related to the acceleration of microparticles to hypervelocities [28] or in removing dust floating inside a plasma reactor [29]. Hypervelocity dust particles can be used as a tool for diagnozing hot plasmas [30] or for quenching instabilities in tokamak plasmas [31].…”
Section: Surface Cleaning By Plasma Jetmentioning
confidence: 99%